Onboard performance of the level 1 trigger of the mini-EUSO telescope. Issue 9 (1st November 2022) - Battisti, M.; Barghini, D.; Belov, A.; Bertaina, M.; Bisconti, F.; Bolmgren, K.; Cambiè, G.; Capel, F.; Casolino, M.; Ebisuzaki, T.; Fenu, F.; Franceschi, M.A.; et al.
Abstract: The Mini-EUSO telescope was launched for the International Space Station on August 22 nd, 2019 to observe from the ISS orbit ( ∼ 400 km altitude) various phenomena occurring in the Earth's atmosphere through a UV-transparent window located in the Russian Zvezda Module. Mini-EUSO is based on a set of two Fresnel lenses of 25 cm diameter each and a focal plane of 48 × 48 pixels, for a total field of view of 44 ° . Until July 2021, Mini-EUSO performed a total of 41 data acquisition sessions, obtaining UV images of the Earth in the 290 nm – 430 nm band with temporal and spatial resolution on ground of 2.5 μs and 6.3 × 6.3 km 2, respectively. The data acquisition was performed with a 2.5 μs sampling rate, using a dedicated trigger looking for signals with a typical duration of tens of μs. In the present paper the analysis of the performance of the 2.5 μs trigger logic is presented, with a focus on the method used for the analysis and the categories of triggered events. The expected functioning of the trigger logic has been confirmed, with the trigger rate on spurious events that remains within the requirements in nominal background conditions. The trigger logic detected several different phenomena, including lightning strikes, elves, ground-based flashers and events with EAS-like characteristics.